CEM: Increasing productivity through the management and monitoring of experiences provided to customers - Adriana Arineli; Heitor Luiz Murat de Meirelles Quintella; Tahir Nisar (Cogent Business & Management, 2015)
Dealing with intangible and so subtle experience is unusual and a huge challenge for management that is not used to measure what has no numbers, but maybe they need to see beyond the obvious and accessible statistics. Recently, several studies point to the importance of customer experience management (CEM). However, if the CEM is a strategy to focus on operations and processes of a business around the customers' experiences with the company, it is essential to seek grants to structure it and find out its effectiveness. This study examines the issues involved in offering superior customer experiences on fashion retail stores in Brazil, identifying the relation between productivity and CEM. Through a research with managers of three important Brazilian clothing retail chains, it was possible to analyze the aspects that impact on the customer experience and their relevance. A questionnaire was applied to evaluate 23 variables that make up the experience of the customer and their impact on increasing productivity. Some statistical techniques were used for data processing and it was possible to realize that only 4 of the 23 items were not relevant for customer experience. It can be concluded that CEM is effective in increasing productivity and can be used as a guideline matrix management in decision-making to promote superior customer experiences. Specific characteristics of each segment suggest different impacts in every aspect. Therefore, it is crucial that each segment review its own variables that will structure the CEM. Even assuming that it is defiant see beyond the obvious, maybe this is the necessary opportunity to create real competitive advantage and longevity for companies that want to stand out and be successful over time.
Keywords: 650